Предмет: Алгебра,
автор: 1634746857
2a(a + b) – b(2a– b) – b(b + 1) при а = - 0,3 и b = - 0,4.
Ответы
Автор ответа:
0
= 2a^2+2ab - 2ab + b^2 -b^2 - b = 2a^2 - b
Если a=-0.3 b= =0,4, то 2 * (-0,3)^2 - (-0,4) = 0.18 + 0.4 = 0.58
Если a=-0.3 b= =0,4, то 2 * (-0,3)^2 - (-0,4) = 0.18 + 0.4 = 0.58
Автор ответа:
0
yt ghfdbkmyj
Автор ответа:
0
неправильно
Похожие вопросы
Предмет: Математика,
автор: nastapopkova014
Предмет: Физика,
автор: abbossherbotayev761
Предмет: Математика,
автор: ivan451113
Предмет: Математика,
автор: пелогелогея13
Предмет: Химия,
автор: LoveangeL125